Understanding Customer Loyalty in QRIS Payment Systems: The Mediating Roles of Satisfaction and Trust Among Generation Z Users of Online Transportation Services - Nailah Muzdalifah GP (JURNAL AKUNTANSI DAN MANAJEMEN, 2026)
This study aims to examine the effects of perceived usefulness and perceived ease of use on customer loyalty in the use of QRIS payment systems within online transportation services, while considering the mediating roles of customer satisfaction and trust among Generation Z users. A survey method was employed, with data collected through an online questionnaire distributed to Generation Z users of QRIS payment systems in online transportation services. A total of 409 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that perceived usefulness has a positive and significant effect on customer satisfaction and trust, while perceived ease of use positively and significantly influences perceived usefulness, customer satisfaction, and trust. Furthermore, customer satisfaction and trust were found to have positive and significant effects on customer loyalty. However, perceived usefulness and perceived ease of use did not exhibit significant direct effects on customer loyalty. The mediation analysis further indicates that customer satisfaction and trust fully mediate the relationships between perceived usefulness, perceived ease of use, and customer loyalty. This study contributes to the advancement of the Technology Acceptance Model (TAM) by providing empirical evidence on how customer loyalty toward QRIS payment systems is developed through satisfaction and trust mechanisms in the context of online transportation services.